2020
DOI: 10.1111/gwat.13008
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Extracted Groundwater Volumes Estimated from Electricity Consumption

Abstract: Land subsidence caused by groundwater overexploitation is a serious global problem. The acquisition of spatiotemporal pumping rates and volumes is a first step for water managers to develop a strategic plan for mitigating land subsidence. This study investigates an empirical formulation to estimate the monthly maximum pumped volume over a 10‐year period based on electric power consumption data. A spatiotemporal variability analysis of monthly pumped volume is developed to provide an improved understanding of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These uncertainties affect the model prediction when the system is heterogeneous from both a spatial and temporal perspective. Chu et al (2020) conducted a study to show the effects of groundwater extraction using pumping and seasonal variations from agricultural usage. Most groundwater in the study region is used for irrigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These uncertainties affect the model prediction when the system is heterogeneous from both a spatial and temporal perspective. Chu et al (2020) conducted a study to show the effects of groundwater extraction using pumping and seasonal variations from agricultural usage. Most groundwater in the study region is used for irrigation.…”
Section: Resultsmentioning
confidence: 99%
“…The SR model does not consider the local effect of human activities or the global effect of hydrological conditions. These uncertainties affect the model prediction when the system is heterogeneous from both a spatial and temporal perspective Chu et al (2020). conducted a study to show the effects of groundwater extraction using pumping and seasonal variations from agricultural usage.…”
mentioning
confidence: 99%
“…16 This method has been implemented to estimate groundwater yield in various contexts. Chu et al 200 used electric power consumption records from pumping wells to estimate monthly groundwater yield over a 10 year period across the Choshui River Alluvial Fan in Taiwan and found that a spatio-temporal variability analysis of groundwater yield volumes is an effective method of identifying the patterns of pumped volumes in a region.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional numerical modeling, these approaches can largely diminish the dependence on forcing data but at the cost of omitting critical physical processes. Due to the lack of observations or adequate information for groundwater modeling (e.g., properties of aquifers), many studies have explored using auxiliary data (e.g., electricity consumption for groundwater pumping) and AI approaches to estimate GWSC based on GWL modeling (Chu et al, 2020;Rajaee et al, 2019;Sun et al, 2020). Shen (2018) showed that AI approaches are more robust than traditional statistical approaches after they are sufficiently trained with large data sets.…”
mentioning
confidence: 99%